Exploring AZO overlay on CZTS/CdS photocathode for solar water splitting - Lim, Nathan Long Jun (Nanyang Technological University, 2020)
One of the earliest photoelectrochemical cell (PEC) demonstrations was done by Fujishima and Honda in 1972 where TiO2 and Pt electrodes were used to produce oxygen and hydrogen gas respectively. However, the poor light absorbing characteristics of TiO2 resulted in poor Solar-To-Hydrogen (STH) efficiency. Kesterite Copper-Zinc-Tin-Sulphide or Cu2ZnSnS4 (CZTS) is one of the more promising materials to be utilized as a photocathode due to its characteristics of having an optimum band gap (1.5eV), high absorption coefficient, p-type behaviour and earth abundant elemental constituents. However, to date, CZTS photocathodes suffer from poor photocurrent and onset potential, and poor stability. To increase photocurrent and enhance stability of the photocathode, the application of a transparent conductive oxide (TCO) overlay deposited on top of the CdS buffer layer is a viable option to explore. This TCO overlay increases the photocurrent and onset potential by enhancing the charge transport efficiency of photogenerated electrons from the CdS buffer layer to the Pt catalyst and increases the stability of the photocathode stack by preventing corrosion prone CdS from being in contact with the electrolyte. Aluminium doped Zinc Oxide (AZO) is a potentially viable TCO overlay due to its high conductivity and optical transmittance. In this project, AZO is deposited on top of CZTS/CdS and together with Pt catalyst is investigated as a photocathode stack. Our CZTS/CdS/AZO/Pt photocathode stack increases the photocurrent at 0 VRHE by 50% and Open Circuit Potential (OCP) by two-fold, resulting in a photocurrent of 1.95mAcm-2 at 0 VRHE and OCP of 0.3V. However, the stability of the CZTS/CdS/AZO/Pt photocathode still suffers from similar degradation during the stability test. Preliminary results indicate that while the AZO does not prevent degradation completely, the degradation rate seems to be reduced with AZO for certain electrolytes. Therefore, further work can be done to improve the photocathode stability through incorporation of another protective layer or changing the electrolyte used.